MODEL RANCANG BANGUN SISTEM INFORMASI SCM PADA INDUSTRI TEKSTIL - Aditya Dwi Bachtiar; Agung Susilo; Yusuf Amrozi (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2021)
The textile industry is an industry that produces various fibers, yarns, fabrics, textile apparel, knitted apparel, textile finished goods and knitted finished goods. One that affects the development of the textile industry is the procurement process in the supply chain system. Supply Chain Management. (SCM) is a network of companies that work together to create and deliver a product to consumers. Some of the constraints of the supply process that often appear these days are delays in the supply of raw materials. To help solve these problems, the construction of SCM information systems in the textile industry was carried out. The method used in this study is qualitative descriptive. By comparing previous research sources, the study offers a design of the SCM model. The results showed the design model of SCM information systems in the textile industry that helps communicate data and information from various lines.